Comprehensive characterization of endometriosis patients and disease patterns in a large clinical cohort - Blum, Simon; Fasching, Peter; Hildebrandt, Thomas; Lermann, Johannes; Heindl, Felix; Born, Tilman; Lubrich, Hannah; Antoniadis, Sophia; Becker, Karina; Fahlbusch, Christine; Heusinger, Katharina; Burghaus, Stefanie; et al. (Archives of Gynecology and Obstetrics, 2021)
Purpose In many diseases, it is possible to classify a heterogeneous group into subgroups relative to tumor biology, genetic variations, or clinical and pathological features. No such classification is available for endometriosis. In our retrospective case-case analysis we defined subgroups of endometriosis patients relative to the type and location of the endometriosis lesion and relative to basic patient characteristics. Methods From June 2013 to July 2017, a total of 1576 patients with endometriosis diagnosed at surgery were included in this study. The patients' history and clinical data were documented using a web-based remote data entry system. To build subgroups, all possible combinations of endometriosis locations/types (peritoneal; ovarian endometriosis; deeply infiltrating endometriosis; adenomyosis) were used. Due to the variation in group sizes, they were combined into five substantial larger groups. Results Age, pregnancy rate, and live birth rate were identified as characteristics that significantly differed between the five patient groups that were defined. No significant differences were noted in relation to body mass index, length of menstrual cycle, age at menarche, reason for presentation, or educational level. Conclusion This study describes basic patient characteristics in relation to common clinical subgroups in a large clinical cohort of endometriosis patients. Epidemiological information about different clinical groups may be helpful in identifying groups with specific clinical courses, potentially suggesting novel approaches to early detection and to surgical and systemic treatment.
CRIS-Team WoS Importer:2021-09-10